2018
DOI: 10.3390/met8050370
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Electrolyte Nature and PEO Process Parameters on Properties of Anodized Ti-15Mo Alloy Intended for Biomedical Applications

Abstract: Plasma electrolytic oxidation (PEO) of Ti-15Mo alloys conducted in electrolytes containing Ca and P compounds can be an efficient process with which to obtain bioactive coatings. This paper reports on the influence of the nature of the electrolyte, its concentration, and PEO process parameters on the properties of anodized layers on Ti-15Mo. A wide range of Ca-and P-containing alkaline and acidic solutions was employed to incorporate Ca and P ions into the anodized layer. The efficiency of the incorporation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The present Special Issue covers 10 papers: Six articles [1][2][3][4][5][6] discuss the Plasma Electrolytic Oxidation PEO of titanium [2,4,6] and its alloys [1,3,5], two papers talk about the PEO processing of aluminum alloys [7] and composites [8], and one on magnesium alloys [9]. The tenth paper is a review regarding soft sparking issues in PEO [10].…”
Section: Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present Special Issue covers 10 papers: Six articles [1][2][3][4][5][6] discuss the Plasma Electrolytic Oxidation PEO of titanium [2,4,6] and its alloys [1,3,5], two papers talk about the PEO processing of aluminum alloys [7] and composites [8], and one on magnesium alloys [9]. The tenth paper is a review regarding soft sparking issues in PEO [10].…”
Section: Contributionsmentioning
confidence: 99%
“…Banakh et al [5] worked to obtain bioactive coatings on Ti-15Mo alloys using PEO treatment in electrolytes containing Ca and P compounds. The studies were performed to reveal the influence of the nature of the electrolyte, its concentration, and PEO process parameters on the properties of anodized layers.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…e paper [15] describes the design and engineering of implant manufacturing using additive technologies. e surfaces of biomaterials are subjected to various modifications to affect their physical and chemical properties as well as allow obtaining optimal surface topography [16], such as coatings on operational surfaces of implants [17][18][19]. ese coatings improve surface properties and create effective compositions for combining different characteristics, such as strength, wear resistance, and blocking unwanted heat fluxes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding corrosion behaviour, studies show that oxide layers obtained by MAO confer about a one to two decade decrease in corrosion kinetics compared to their Ti or Ti alloy base materials, together with a substantial increase in corrosion potential [7,[13][14][15][16]. On the other hand, biological behaviour studies have shown that MAO layers can have improved cell adhesion, proliferation, and differentiation, as well as antimicrobial properties [4,6,7,[17][18][19][20][21]. Several reports are also available on the tribocorrosion behaviour; however, most of them only report on the evolution of open circuit potential under sliding action, without considering the corrosion kinetics, whereas very little is known about the evolution of kinetics during mechanical action [22,23].…”
Section: Introductionmentioning
confidence: 99%